Answer:
Step-by-step explanation:
We are given the two functions:
And we want to find:
So, by substitution, we acquire:
Distribute:
Simplify:
Answer:
Step-by-step explanation:
Given:
The given inequality is.
Solution:
Simplify the given expression.
Multiply by x both side of the equation.
Simplify.
Rewrite the equation as.
Therefore, is the simplest form of the given expression.
Answer:
1/5, 1/6, 1/7, 1/8
Step-by-step explanation:
The formula for the sequence is (n+3)!/ (n+4)!
The first terms uses n=1
a1 = (1+3)!/ (1+4)! = 4!/5! = (4*3*2*1)/(5*4*3*2*1) = 1/5
The first terms uses n=2
a2 = (2+3)!/ (2+4)! = 5!/6! = (5*4*3*2*1)/(6*5*4*3*2*1) = 1/6
The first terms uses n=3
a3 = (3+3)!/ (3+4)! = 6!/7! = (6*5*4*3*2*1)/(7*6*5*4*3*2*1) = 1/7
The first terms uses n=4
a4 = (4+3)!/ (4+4)! = 7!/8! = (7*6*5*4*3*2*1)/(8*7*6*5*4*3*2*1) = 1/8
Angle B=180-(38+31.6)=110.4
by law of sin
sin B/b=sinA/A
sin(110.4)/b=sin38/25
b=25*sin(110.4)/sin(38)=38.06
Not positively sure but I believe it goes like this
Answer: 9x+26+5x=180
14x+26=180
180-26=14x
14x=154
X=15